Dialog religijny w świetle Bożego Słowa - Rossa, Piotr (Uniwersytet im. Adama Mickiewicza; Wydział Teologiczny, 2011)
The article presents dialogue as the most basic phenomenon which takes place in the life of man who is understood as homo-religiosus, situated primarily within the experience of an encounter between man and God. The presence of the Word of God in the world, in the areas of culture and media, for instance, has had a good and effective influence on the relationships which are present in the world. The word of God inspires us to defend the rights of man, to live a life in freedom by introducing justice and peace into international relations. It also reminds us of the importance of protecting the natural environment. At the heart of the word of God there is Divine Revelation in its interpersonal dimension, whose summit and fullness is Jesus Christ Himself. This mutual existence of God and man, made complete in Jesus Christ, finds its extension in creation. That is why both an encounter and dialogue with all people of good will and persons of various religious traditions constitutes a foundation for the Church’s activity. It is from this foundation that the article draws the theme of dialogue between Christianity and the great religions of the world, with particular attention being given to Islam, while presenting contemporary Church pronouncements on this subject as well as Christianity’s tasks in the field of interreligious dialogue for the future.
Religious Dialogue in Light of the Word of God
Keywords: Objawienie; Revelation; Jezus Chrystus; Jesus Christ; Kościół; Church; dialog międzyreligijny; Interreligious dialogue; dialogo interreligioso; Islam; wolność; freedom; Vatican Council II; Sobór Watykański II; Concilio Vaticano II; Jan Paweł II; John Paul II; Иоанн Павел II; dialogue interreligieux; Benedykt XVI; Benedict XVI; „Verbum Domini”; “The Word of God”; 本笃十六世; ベネディクト16世; बेनेडिक्ट XVI